Why did Argentina become a super-exporter of agricultural and food products during the Belle Époque (1880-1929)? - Vicente Pinilla; Agustina Rayes (European Historical Economics Society (EHES), 2017)
The objective of this paper is to explain, from a cliometric perspective, the determinants of the growth of Argentina's exports between 1880 and 1929. To do this, we have constructed a gravity model with the principal products exported each year by Argentina to its most important trading partners. In this way, we believe that this study constitutes a relevant and original contribution to the analysis of economic growth from a historical perspective and specifically in explaining the factors determining the export success of the settler countries during the first wave of globalisation. Our results show that Argentina's export-led growth must be explained from both the supply and demand sides. We also find that the reduction in transatlantic transport costs boosted exports.
Keywords: F14; N56; N76; Q17; 330; Settler Economies; Economic History of Argentina; First Globalization; Trade Gravity Models; Latin America Economic History